2021
DOI: 10.1007/s11523-021-00810-9
|View full text |Cite
|
Sign up to set email alerts
|

Bintrafusp Alfa, a Bifunctional Fusion Protein Targeting TGFβ and PD-L1, in Patients with Esophageal Squamous Cell Carcinoma: Results from a Phase 1 Cohort in Asia

Abstract: Background Patients with esophageal squamous cell carcinoma (SCC) have limited treatment options. Blocking transforming growth factor-β (TGFβ), which can be overexpressed in these tumors, may enhance responses to programmed cell death protein 1/programmed death-ligand 1 [PD-(L)1] inhibitors. Bintrafusp alfa is a first-in-class bifunctional fusion protein composed of the extracellular domain of the TGFβ receptor II (TGFβRII) (a TGFβ "trap") fused to a human IgG1 monoclonal antibody blocking PD-L1. Objective The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Importantly, skin lesions, such as keratoacanthomas, are anticipated AEs for TGF-β inhibition [ 49 ]. The overall safety profile reported here for bintrafusp alfa in esophageal AC was consistent with those previously observed with bintrafusp alfa treatment in other solid tumors, including esophageal SCC [ 23 , 24 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Importantly, skin lesions, such as keratoacanthomas, are anticipated AEs for TGF-β inhibition [ 49 ]. The overall safety profile reported here for bintrafusp alfa in esophageal AC was consistent with those previously observed with bintrafusp alfa treatment in other solid tumors, including esophageal SCC [ 23 , 24 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, all but one response occurred in immune-excluded tumors in this esophageal AC cohort. Similar results were also observed in patients with esophageal SCC from the other study, in which responses were seen exclusively in immune-excluded tumors [ 39 ]. Taken together, the results of the exploratory analyses did not identify predictive biomarkers of response to bintrafusp alfa in this small cohort.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In preclinical models, BA was shown to activate both the innate and adaptive immune systems and provide long-term protective antitumor immunity, reduce metastasis and fibrosis, and be an effective combination partner with radiation or chemotherapy [ 33 , 34 ]. In phase I clinical trials in patients with advanced solid tumors, BA showed early evidence of clinical activity [35] , [36] , [37] , [38] , [39] , [40] .…”
Section: Introductionmentioning
confidence: 99%